Upaya meningkatkan minat belajar siswa melalui media dadu games pada mata pelajaran Al-Qur’an Hadits Kelas XI MAN 2 Jombang - Herman, Silvia Isna Auladah (Maliki Interdisciplinary Journal, 2024)
Lack of attention and activeness of students in learning is a problem that should be resolved. The application of the lecture method in learning Al-Quran Hadith makes students show bored and sleepy attitudes in teaching and learning activities. This is because learning is teacher-centered. Students become passive people who only listen to the teacher’s explanation. The existence of research results like that requires the application of new learning strategies in Al-Quran Hadith lessons. The research was written using the classroom action research method. Data collection methods include observation and tests. The research results showed that students showed an increase in their interest in learning.